Unravelling molecular mechanism of oral squamous cell carcinoma and genetic landscape: an insight into disease complexity, available therapies, and future considerations - Shebbo, Salima; Alateyah, Nooralhuda; Yassin, Esraa; Mahmoud, Doaa El Sayed; Tamimi, Faleh; Anweigi, Lamyia; Elhissi, Abdelbary; Abou-Saleh, Haissam; Elrayess, Mohamed A.; Agouni, Abdelali (Frontiers in Immunology, 2025)
Oral squamous cell carcinoma (OSCC) is a heterogeneous malignant neoplasm characterized by intricate molecular pathways and a varied genetic landscape, resulting in a diminished 5-year survival rate. Due to this complexity, many trials of emerging therapies are failing to improve the outcome and survival rate of OSCC, posing a great challenge in the management of this cancer. This review examines the key molecular pathways, genetic susceptibility, and the influence of the microbiome in the advancement of OSCC. Furthermore, it analyses contemporary therapeutic approaches, their limitations, and prospects, especially the incorporation of immunotherapy. The discussion will also encompass the difficulties in turning research findings into successful therapeutic applications and enhancing the patient’s quality of life.